(untitled) (Revista de Ciências Agroveterinárias, 2018)
Environmental modifiers, such as the use of water blade, are often used to produce pigs in order to improve welfare conditions and consequently production. In view of this consideration, we sought to evaluate the effect of the climatic environment on the weight gain and the behavior of pigs in the finishing phase in stalls with and without access to the water blade. The work was conducted in a pig farm located in the city of Nova Porteirinha, located in the semi-arid region of Minas Gerais. In order to evaluate the thermal comfort of the animals, the Black Globe Temperature and Humidity Index (BGHI) was used to evaluate the thermal comfort of the animals and to analyze the behavior of the pigs, the number of animals performing the activity, for the period evaluated, as well as the gain of weight were observed. In the 3rd block, black globe temperature and humidity index values were higher, with lower average daily weight gain. The treatments resulted in different behavioral responses, with water blade behavior being more expressive in the afternoon. The evaluation period showed that to influence surface temperature and at high temperatures the animals presented lower daily average weight gain. The water table did not influence the animals’ weight gain, however, it provided better welfare conditions.